An overview of the history and development of naturopathy in South Africa - Wendy G. Ericksen-Pereira; Nicolette V. Roman; Rina Swart (AOSIS, 2018)
Background: A huge growth in complementary and alternative medicine (CAM) took place in South Africa in the 1960s which paralleled what was happening in other parts of the western world. Naturopathy has been practised in South Africa for over 60 years, and the history of naturopathy is entwined with the broader history of CAM. No laws existed at that stage to regulate the curriculum, education and training of CAM practitioners. With the passage of time, various statutes were introduced which eventually led to changes in legislation and the establishment of a recognised training programme. Naturopathy became a legally regulated profession, the full history of which has never been documented.   Objective: This article explores the history of naturopathy in South Africa.   Method: A two-phase qualitative research design was used, consisting of a document search and semi-structured interviews with key informants who were identified through a process of snowballing. Information collected from the naturopaths who participated in the interviews was triangulated with documentation uncovered in the archives of the Allied Health Professions Council of South Africa (AHPCSA) and other literature available. Results: The result is a history of events which took place and reveals the effect of various legislations on the profession.   Conclusion: Changes in the political system paved the way for changes in legislation which allowed for the registration and training of naturopathic practitioners. However, the lack of a functioning association and the small number of naturopathic graduates have hampered the growth of the profession, preventing it from becoming a significant contributor to the health care system.